2020
DOI: 10.1186/s13012-020-00990-4
|View full text |Cite
|
Sign up to set email alerts
|

The Balanced Opioid Initiative: protocol for a clustered, sequential, multiple-assignment randomized trial to construct an adaptive implementation strategy to improve guideline-concordant opioid prescribing in primary care

Abstract: Background: Rates of opioid prescribing tripled in the USA between 1999 and 2015 and were associated with significant increases in opioid misuse and overdose death. Roughly half of all opioids are prescribed in primary care. Although clinical guidelines describe recommended opioid prescribing practices, implementing these guidelines in a way that balances safety and effectiveness vs. risk remains a challenge. The literature offers little help about which implementation strategies work best in different clinica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The study includes four embedded implementation strategies (Table 2), two of which were adaptive based on response to phase 1 strategies [49][50][51]. The primary aim was to test whether the least intensive strategy-REP alone-versus the adaptive implementation strategy in Fig.…”
Section: Primary and Secondary Aims And Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study includes four embedded implementation strategies (Table 2), two of which were adaptive based on response to phase 1 strategies [49][50][51]. The primary aim was to test whether the least intensive strategy-REP alone-versus the adaptive implementation strategy in Fig.…”
Section: Primary and Secondary Aims And Hypothesesmentioning
confidence: 99%
“…Given that there is substantial heterogeneity in terms of implementation barriers at schools [48] and in how different schools might respond to different combinations of strategies, there is a need to develop and evaluate effective adaptive implementation strategies [49][50][51]. An adaptive implementation strategy is a sequence of decision rules used to guide implementers in selecting which combination of implementation strategies (e.g., REP, Coaching, Facilitation) to offer and when, including considerations of a school's changing needs.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the needs of all clinics, implementers need better guidance from implementation scientists on how to select and “prescribe” the choice of initial strategy(ies) with greater precision. Similarly, implementers could also benefit from guidance on how to monitor the success of strategies early on, and how to subsequently adapt or alter the strategy(ies) being offered depending on such measures of success or failure [ 67 , 68 ]. The findings also begin to point to the importance of building packages of implementation strategies that are successful at engaging clinics [ 27 , 69 , 70 ], or that monitor clinics for early signs of disengagement and then course-correct if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggested that the most cost-effective implementation support starts with a less intensive, less costly implementation strategy and increases as needed to enhance EBP uptake [ 22 ]. A SMART design is also being applied to the implementation of clinical guidelines for opioid prescribing in primary care settings, in which clinics are randomized to receive a sequence of implementation strategies that address implementation concerns at the health system, clinic, and provider levels [ 32 ]. This ongoing study aims to identify the most cost-effective sequence and combination of implementation strategies [ 32 ].…”
Section: Methodsmentioning
confidence: 99%